Differential regulation of eicosanoid and endocannabinoid production by inflammatory mediators in human choriodecidua - Mitchell, Murray D.; Rice, G. E.; Vaswani, K.; Kvaskoff, David; Peiris, H. N. (PLOS ONE, 2016)
An increase in intrauterine prostaglandin production is critical for the onset and progression of labor in women and indeed all mammalian species studied. Endocannabinoids can act as substrates for enzymes of the prostaglandin biosynthetic pathways and can be utilized to generate other related compounds such as prostamides. The end products are indistinguishable by radioimmunoassay. We have separated such compounds by mass spectrometry. We now show that inflammatory stimuli such as LPS and proinflammatory cytokines act differentially on these pathways in human choriodecidua and preferentially create drive through to prostaglandin end products. These findings create doubt about the interpretation of data on prostaglandin biosynthesis in intrauterine tissues from pregnant women especially in the presence of an infection. The possibility is raised that separation of these products might reduce variability in results and lead to potential uses for their measurement in the diagnosis of preterm labor.
Gesehen am 23.06.2020